A system for quality assessment of forestry contractors - Triplat, Matevž (Array, 2020)
Skilled contractors are needed to meet the increased demand for wood and to maintain a competitive edge in forestry. The structure of the forest industry has changed significantly. Today"s situation favours smaller contractors that are more flexible. Worldwide contractors are important for forest operations, but there is often limited knowledge about how well they fulfil demands about resource efficiency, social responsibility and environmental protection. The aim of this paper is to present the guidelines for the assessment of forestry contractors following sustainability principles and to present a recently developed system. In addition to the requirements for professional competences and legislative obligations, the system proposes a number of additional requirements such as corporate social responsibility, participation in the local community and greater environmental responsibility. The forestry contractor and the certification body sign a cooperation agreement to obtain the expert assessment. The expert assessment is performed by an evaluator authorised by a certification body. A web service has been introduced with the purpose of serving as a communication tool between professional evaluators and forestry contractors, as well as providing a new possibility for forest owners to get direct contact with forestry contractors. The system enables its users to exert influence on the assessment of forestry contractors by assessing the quality of their services. Private forests would greatly benefit from customer feedback information on the service quality. By now, 1584 forest contractors have registered in Slovenia, where 67% provide the service of cutting and skidding, 8% provide woodchipper service, 7% transport of round wood, 5% cable crane yarding and 4% fully mechanised harvesting. Until June 2020, 142 forest contractors have gone through the process of quality assessment.